1992
DOI: 10.1017/s0022029900027175
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of 3-deoxypentulose and its determination in heated milk

Abstract: SummaryThe presence of 3-deoxypentulose in heated milk is reported. This compound has been isolated from alkaline solutions of lactose and characterized by spectroscopic and Chromatographie techniques. Gas Chromatographic analysis of free monosaccharides of milk revealed two peaks corresponding to 3-deoxypentulose in commercial sterilized milk samples, in a concentration range of 30–50 mg/1. Its concentration increased with temperature and length of time of processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Among deoxysugars, 3-deoxypentulose was firstly identified by GC in heated milk as its TMS ether, which was prepared with TMSI:TMCS (2:1) in pyridine at room temperature [95]. ␣-Dicarbonyl sugars have been extensively studied.…”
Section: Derivatives Of Intermediate Compoundsmentioning
confidence: 99%
“…Among deoxysugars, 3-deoxypentulose was firstly identified by GC in heated milk as its TMS ether, which was prepared with TMSI:TMCS (2:1) in pyridine at room temperature [95]. ␣-Dicarbonyl sugars have been extensively studied.…”
Section: Derivatives Of Intermediate Compoundsmentioning
confidence: 99%
“…Other possible reaction products of this derivative such as 3-deoxypentulose, as ketose derivatives, or furfuryl alcohol have been found in model systems and food, e.g., in heat-treated milk. For example, Troyano et al (18) published the formation of 3-deoxypentulose in milk and in alkaline model mixtures containing maltose or cellobiose. Formic acid was also proposed as a secondary product.…”
Section: Hydrothermolysis Of Oligomeric Carbohydratesmentioning
confidence: 99%
“…The degradation of lactulose also results in the formation of several C5 compounds. In addition to the formation of furfural and furfuryl alcohol, as discussed earlier, the formation of 3-deoxypentosulose (Troyano et al, 1992a) and deoxyribose (Berg, 1993) has been reported.…”
Section: Lactulosementioning
confidence: 68%